Emendas parlamentares ao orçamento federal do SUS: Método para estimaç\~ao dos repasses a cada município favorecido, segundo áreas de alocaç\~ao dos recursos (2015-2020) - Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– The allocation of federal resources through parliamentary amendments (PA) to the Unified Health System (SUS) has been growing since the budget execution of these resources became mandatory, contributing to the reduction of the share of resources allocated to public health actions and services (ASPS) by the Ministry of Health (MS) programming. In addition, deficits in transparency in the budgetary-financial execution of these resources have made it difficult to account the expenses by areas of operation of the SUS. So, the objective of this text is to propose a method for estimating expenditure on public health actions and services (ASPS) through parliamentary amendments (PA) of the Ministry of Health (MoH), with each municipality favored, according to areas of resource allocation, from 2015 to 2020. It is a contribution to future studies on financing and public spending on health in Brazil. To this end, the methodological investigation was based on an exploratory analysis of the MoH budget-financial execution reports from 2015 to 2020. Three sources of information were used: i) Siga Brasil: information system on the Union budget, which is maintained by the Federal Senate; ii) an electronic spreadsheet provided by the National Health Fund (NHF), obtained from a request for access to information, containing data on execution by PA; and iii) the NHF Parliamentary Amendments Panel, which provides data on PA execution by the MoH on the internet. The procedures for identifying expenses by PA in Siga Brasil were detailed. The result of the report analysis of each these three sources was that, according to the criteria of accessibility, methodological clarity, coverage, and consistency, Siga Brasil is the most adequate source for obtaining information on expenses by PA of the MoH with each favored municipality. Procedures for estimating expenditure on primary and medium and high-complexity care for the period from 2015 to 2018 were proposed, obtaining, in the end, the expenditure by PA of the MoH with each municipality, according to these and other areas of resource allocation, for the entire period investigated (2015 to 2020). It is concluded that the proposed method is feasible and reproducible, but that problems in the registration of expenditures by the federal public administration affect the transparency and quality of information, especially for the years 2015 and 2016.
Keywords: H51; I18; 330; health expenditures; budgets; health care rationing; federal government; Unified Health System